Potential benefits of yeast Saccharomyces and their derivatives in dogs and cats: a review - Maturana, Marta; Castillejos, Lorena; Martin-Orue, Susana M.; Minel, Anaelle; Chetty, Olivia; Felix, Ananda P.; Adib Lesaux, Achraf (Frontiers in Veterinary Science, 2023)
Yeast Saccharomyces and its derivatives have been largely used in livestock and poultry nutrition for their potential positive impact on growth, performance, and general health.Originally included in animal diets as a source of protein, yeasts can also offer a wide range of by-products with interesting bioactive compounds that would confer uses beyond nutrition.Although its supplementation in livestock, poultry and even in humans is well documented, the available body of literature on the use of yeast and its derivatives in companion animals' food, mainly dogs and cats' diets, is still developing. Despite this, gut microbiota modulation, immune system enhancement or decreasing of potentially pathogenic microorganisms have been reported in pets when using these products, highlighting their possible role as probiotics, prebiotics and postbiotics. This review attempts to provide the reader with comprehensive view on the effects of Saccharomyces and its derivatives in pets and the possible mechanisms that confer their functional properties.